Incorporation of several additives into gluten free breads: Effect on dough properties and bread quality - Sciarini, Lorena Susana (2012)
The objective of this work was to assess the effect of emulsifiers, hydrocolloids and enzymes on gluten-free dough rheology and thermal properties and bread quality, while relating dough properties parameters to bread technological quality. Breads were based on rice flour, cassava starch and full-fat active soy flour, with 65% or 75% (flour-starch basis) of water incorporation. Additives used were emulsifiers (diacetyl tartaric acid ester of monoglycerides - DATEM and sodium stearoyl lactylate - SSL), enzymes (glucose oxidase and α-amylase) and hydrocolloids (xanthan gum, carboxymethylcellulose, alginate and carrageenan). Results showed that additive incorporation modified dough behavior, evidenced by different calorimetric and rheological properties. Besides, the electrophoretic pattern of dough extracted proteins changed with glucose oxidase addition. These modifications resulted in breads with different characteristics, such as specific volume, firmness and firming rate, and crumb structure. Nonetheless, they did not necessarily show better quality parameters than the control bread. The control dough displayed good performance for obtaining gluten-free breads of acceptable volume, crumb structure and, principally, with lower hardening rate during storage. Contrary to widespread opinion, this work shows that the presence of additives is not essential for gluten-free bread production. This fact provides new perspectives to the gluten free market at the moment of selecting raw materials and technological parameters, reducing production costs and facilitating gluten free products development.